2014
DOI: 10.3892/ijmm.2014.1623
|View full text |Cite
|
Sign up to set email alerts
|

Expression of retinoic acid target genes in coronary artery disease

Abstract: Coronary atherosclerosis can lead to myocardial infarction, and secondarily to post-infarct remodelling and heart failure. Retinoic acid (RA) influences cell proliferation. We hypothesized that RA could influence gene expression and proliferation of cardiovascular cells. Left ventricular biopsies from patients with end-stage heart failure due to coronary artery disease (CAD) or dilated cardiomyopathy were investigated for the content of RA metabolites using liquid chromatography mass spectrometry (LC-MS/MS), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…20 In another study by Bilbija et al, an overexpression of retinoic acid target genes was shown in coronary artery disease (CAD). 24 Bilbija et al also reported that atRA has antiproliferative effects on cardiomyocytes and cardiofibroblasts and concluded that the antiproliferative effects of atRA may be beneficial because it may be used to delay cardiomyocyte remodeling, reduce restenosis and preserve the functions of the cardiovascular system. 24 But in none of the related studies are the underlying signal transduction pathways, which lead to AS reduction and inhibition, clearly defined.…”
Section: Discussionmentioning
confidence: 99%
“…20 In another study by Bilbija et al, an overexpression of retinoic acid target genes was shown in coronary artery disease (CAD). 24 Bilbija et al also reported that atRA has antiproliferative effects on cardiomyocytes and cardiofibroblasts and concluded that the antiproliferative effects of atRA may be beneficial because it may be used to delay cardiomyocyte remodeling, reduce restenosis and preserve the functions of the cardiovascular system. 24 But in none of the related studies are the underlying signal transduction pathways, which lead to AS reduction and inhibition, clearly defined.…”
Section: Discussionmentioning
confidence: 99%
“…The formation mechanisms of AS are complex and numerous, and the structural and functional damage of the vascular endothelium is regarded as the initial step for the genesis of AS (21,22), which influences the AS lesion degree (23,24). It is established that under the action of numerous AS risk factors, including hyperlipidemia, hypertension, diabetes and smoking, the endothelial function is damaged and may be aggravated gradually with AS development (25).…”
Section: Discussionmentioning
confidence: 99%
“…In a subset of patients, acitretin may cause hyperlipidemia, which should be actively treated to avoid increased cardiovascular risk. Previous studies in humans and animals have shown that retinoids may improve and ameliorate the formation of atherosclerotic plaques [ 255 , 256 , 257 , 258 , 259 , 260 , 261 ]. Further investigations are required to determine whether treatment of psoriasis patients with retinoids may prevent the development of atherosclerosis and decrease the risk of cardiovascular events.…”
Section: Effects Of Anti-psoriasis Therapies On Cardiovascular Commentioning
confidence: 99%